PKM Sosialisasi Peraturan Petanque FIPJP Pada Atlet Riau - Joni Alpen; Febria, Rhani; Apriani, Leni; Pradana, Yustin; Effendi, Sahrul (FLEKSIBEL: Jurnal Pengabdian Masyarakat, 2025)
Abstract Petanque is a rapidly growing sport in Indonesia, including in Riau Province. As the popularity of this sport increases, a good understanding of the rules set by the Fédération Internationale de Pétanque et Jeu Provençal (FIPJP) is very important for athletes to be able to compete professionally. However, many athletes in Riau still do not understand the latest rules, which can affect their performance in official matches. This program aims to improve the understanding of petanque athletes in Riau regarding FIPJP regulations through interactive and practice-based socialization. The methods used include Observation, discussion, and Direct Practice. It is hoped that through this activity, athletes can apply the rules better in competitions and improve the quality of their game. Based on the results obtained, this socialization has proven effective in improving the understanding of petanque athletes in Riau. Therefore, it is recommended that similar activities be carried out periodically with a wider scope, such as involving coaches, referees, and other petanque communities. In addition, related sports federations can support this educational program by providing regulatory materials that are more easily accessible to athletes.